Liquid Chromatography Assay for Routine Monitoring of Cellular Ribavirin Levels in Blood - Inoue, Yoichi (American Society for Microbiology, 2004)
Ribavirin-induced hemolytic anemia is one cause for cessation of combination therapy with alpha interferon 2b and ribavirin for hepatitis C infection. Determining cellular ribavirin levels in blood, including the levels of its phosphorylated metabolites, might be useful for predicting ribavirin-induced anemia, because the metabolites accumulate in erythrocytes. We simplified an assay method developed previously to make it suitable for routine monitoring of cellular ribavirin. Whole blood diluted with a sixfold volume of ice-cold distilled water was subjected to acid phosphatase digestion to convert phosphorylated ribavirin metabolites to free ribavirin. The resulting mixture, spiked with an internal standard, was treated by phenyl boronic acid column extraction, followed by reverse-phase high-performance liquid chromatography analysis. The calibration curve for ribavirin levels in whole blood was linear at concentrations of 5.3 to 1,024 μM (r(2) = 0.9999). Validation coefficients of variation for intra- and interday assays were 2.9 to 5.8% and 4.3 to 8.3%, respectively. We tested this method by monitoring blood ribavirin concentrations in two hepatitis C patients receiving alpha interferon 2b-plus-ribavirin combination therapy.